ON GENERALIZATIONS OF DRAGOMIR-AGARWAL INEQUALITY VIA SOME EULER-TYPE IDENTITES - Pečarić, Josip; Vukelić, Ana (Matematichki Bilten, 2002)
Some generalizations of Dragomir-Agarwal inequality are given, by using some Euler-type identities.